Different treatment options for Takayasu arteritis patients with moderate-to-severe aortic regurgitation: long-term outcomes. (30th November 2020) - Cheng, Xuesen; Li, Zuozhi; Dang, Aimin; Lv, Naqiang; Chang, Qian; Song, Yunhu; Liu, Guozhang
Abstract: Objectives: To determine the prognosis of Takayasu arteritis (TA) patients with moderate-to-severe aortic regurgitation treated with surgical vs conservative treatment and to identify independent prognostic factors of long-term outcomes. Methods: Between January 2002 and January 2017, 101 consecutive TA patients with moderate-to-severe aortic regurgitation treated with either surgical ( n = 38) or conservative ( n = 63) treatments were investigated in this retrospective observational case–control study. The primary end point was all-cause mortality, and the secondary end point comprised the combined end points of death, non-fatal stroke and cardiac events (non-fatal myocardial infarction and congestive heart failure). Propensity score matching was used to reduce the bias of baseline risk factors. Results: The unadjusted all-cause 10-year mortality in the conservative group was increased compared with the surgical group (28.2% vs 7.4%; log-rank P = 0.036), and the combined end points showed the same trend (52.1% vs 25.3%; log-rank P = 0.005). After an adjustment of baseline risk factors, the conservative treatment was associated with reduced survival rates of both all-cause mortality [hazard ratio (HR): 8.243; 95% CI: 1.069, 63.552; P = 0.007] and combined end points (HR: 6.341; 95% CI: 1.469, 27.375; P = 0.002). Conservative treatment (HR: 3.838, 95% CI: 1.333, 11.053; P = 0.013) and left ventricular end-diastolic diameter (HR: 1.036, 95% CI: 1.001, 1.071; P = 0.042) were risk factors for increased combined end points. Conclusion: Surgical treatment improves the outcomes of patients with moderate-to-severe aortic regurgitation due to TA. The dilated left ventricle indicated a worse prognosis.